Loss of protein phosphatase 2A regulatory subunit PPP2R5A is associated with increased incidence of stress-induced proarrhythmia - Pluteanu, Florentina; Glaser, Dennis; Massing, Fabian; Schulte, Jan S.; Kirchhefer, Uwe (Frontiers in Cardiovascular Medicine, 2024)
Background: Protein phosphatase 2A (PP2A) is a serine/threonine-selective holoenzyme that controls Ca 2+ homeostasis and contractility of the heart via dephosphorylation of regulatory proteins. In some genetically modified mouse models with increased arrhythmogenicity, a reduced expression of the regulatory subunit B56α of PP2A was found as a concomitant effect. Whether there is a general correlation between the abundance of B56α and the promotion of cardiac arrhythmogenesis remains unclear.Methods: The aim of this study was therefore to investigate the role of PP2A-B56α in the propensity for arrhythmic activity in the heart. The experimental analysis of this question has been addressed by using a mouse model with deletion of the PP2A-B56α gene, PPP2R5A (KO), in comparison to wild-type animals (WT). Evidence for arrhythmogenicity was investigated in whole animal, isolated heart and cardiomyocytes by ECG, recording of monophasic action potential (MAP) induced by programmed electrical stimulation (PES), measurement of Ca 2+ transients under increased pacing frequencies and determination of total K + channel currents (IK) Results: ECG measurements showed a prolongation of QT time in KO vs WT. KO mice exhibited a higher rate of premature ventricular contractions in the ECG. MAP measurements in Langendorff-perfused KO hearts showed increased episodes of ventricular tachyarrhythmia induced by PES. However, the KO hearts showed values for MAP duration that were similar to those in WT hearts. In contrast, KO showed more myocardial cells with spontaneous arrhythmogenic Ca 2+ transient events compared to WT. The whole-cell patch-clamp technique applied to ventricular cardiomyocytes revealed comparable peak potassium channel current densities between KO and WT.Conclusion: These findings support the assumption that a decrease or even the loss of PP2A-B56α leads to an increased propensity of triggered arrhythmias. This could be based on the increased spontaneous Ca 2+ tansients observed.